2004
DOI: 10.1063/1.1691500
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of resistivity in Cu thin films by partial oxidation: Microstructural mechanisms

Abstract: We report the electrical resistance and microstructure of sputter deposited copper thin films grown in an oxygen containing ion-beam sputtering atmosphere. For films thinner than 5 nm, 2-10% oxygen causes a decrease in film resistance, while for thicker films there is a monotonic increase in resistivity. X-ray reflectivity measurements show significantly smoother films for these oxygen flow rates. X-ray diffraction shows that the oxygen doping causes a refinement of the copper grain size and the formation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…To calculate the grain size distribution of the FePt particles, the entire XRD data set was fitted to a model where the peak shapes contain contributions from non-uniform strain and grain size broadening. 28 The shape of each diffraction peak shape was then a convolution of the shapes due to grain-size broadening, which was assumed to originate from a lognormal distribution of grain sizes, [29][30] and to non-uniform strain, which was assumed to be Gaussian:…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the grain size distribution of the FePt particles, the entire XRD data set was fitted to a model where the peak shapes contain contributions from non-uniform strain and grain size broadening. 28 The shape of each diffraction peak shape was then a convolution of the shapes due to grain-size broadening, which was assumed to originate from a lognormal distribution of grain sizes, [29][30] and to non-uniform strain, which was assumed to be Gaussian:…”
Section: Methodsmentioning
confidence: 99%
“…For applications where Ohmic losses are to be minimized, the role of solutes is largely a deleterious one, with the reduction in grain size and increased alloying content leading to interface and impurity scattering, respectively [12][13][14][15]. Correspondingly, thermal annealing of pure Cu is generally employed to reduce electrical resistivity during processing [13].…”
mentioning
confidence: 99%
“…14 Prater et al found that low concentrations of oxygen in the sputtering atmosphere reduced grain size, smoothed the interface and reduced the resistivity of ion-beam deposited Cu thin films. 15 To summarize the previous work, spin-valve GMR and resistivity have been improved by the introduction of oxygen under various concentrations during sputtering and for different film deposition processes. It appears that oxygen favorably alters the film microstructure and smoothes the interfaces, which increases specular scattering of conduction electrons at the interfaces.…”
mentioning
confidence: 99%
“…Some work indicates that oxygen acts as a surfactant floating out on the growing surface, 8,9,11 while Miura et al and Prater et al proposed that the oxygen is incorporated in the film. 10,15 Hence, the mechanism of interface smoothing is still unknown and is, perhaps, dependent on oxygen concentration and film processing.…”
mentioning
confidence: 99%